Letter to the editor concerning “A meta-analysis and systematic review of the clinical efficacy and safety of platelet-rich plasma combined with hyaluronic acid (PRP + HA) versus PRP monotherapy for knee osteoarthritis (KOA)” - Marc A. Russo (Journal of Orthopaedic Surgery and Research)
Abstract Platelet-rich plasma (PRP) is commonly used alone or in combination with hyaluronic acid (HA) in the treatment of knee osteoarthritis. A recently published meta-analysis and systematic review compared outcomes between PRP + HA combination therapy and PRP monotherapy. This letter addresses a critical concern with the study and seeks clarification from the authors.